Utilization of food industry by-products in producing high added value foods: a review - Ensaf, M. Khalil; Sahar, A. Arafa; Khaled, M. Nematalla (Food Technology Research Journal)
Industrialized production demanded higher production volumes and the traditional by-products were replaced by commercial products of low cost and high efficiency. The new production methods, along with the increase in the number of food industry factories and the increase in production volume, resulted in an exponential increase in waste. As legal, environmental and economic issues have been reconsidered in the past two decades, it has become more and more obvious that disposal and landfilling of those wastes present environmental and social drawbacks. At the same time, advances in modern chemistry and biotechnology, academic awareness and industrial interest are helping the study of these wastes. The objective of this article is to present the utilisation of some food industry by-products that have a high environmental load and cause disposal problems for food factories when producing high-added-value foods from these wastes with high nutritional values and economic impact.